An Experimental Study of Collection ,Separation , Enumeration and Cryopreservation of Umbilical Cord Blood Stem Cells - Mutlak, B. H.; Mnati, I. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Umbilical cord blood (UCB) contains hematopoietic and mesenchymal stem cells(HSCs,MSCs) that have proven useful clinically to reconstitute the hematopoietic system in children and some adults . Fifteen cord blood samples were collected from placenta of newly delivered women in AlKadhemia hospital in Baghdad for normal vaginal delivery. Mono nucleated cells (MNCs) were isolated by using density gradient centrifugation and the MNCs count and viability were determinated by trypan blue.MNCs were cryopreserved using the cryoprotectant solution of 10% concentration of dimethyl sulfoxid (DMSO)using slow cooling and rapid thaw. The aim of the present study is to collect, separate and enumerate the stem cells in cord blood(CB) and study the effect of cryopreservation on stem cells count and viability. The results of the present study showed that the average cord blood volume collected was 81.66 ml. Mononuclear cell count ranged from 5.6-14.6 x106.Viability count of mononuclear cells was 93.9%.After three months of cryopreservation , the viability count on revival was 73.9%.This study represents an attempt to isolate the stem cells from UCB. The results of the present study confirmed that UCB provides a great source of stem cells for using in medical applications.